A MODEL FOR DEVELOPING THE COMMUNITY HEALTH NETWORK - Xinxin, Wang (Asia Pacific Journal of Religions and Cultures, 2025)
This study examines the local history, economic status, social culture and other aspects of Don Wai Floating Market, Nakhon Pathom Province. The history of the Don Wai Floating Market, Nakhon Pathom Province was investigated to learn more about its background and development. Strengthening community health governance is an inevitable requirement for implementing the idea of people-centered development and promoting the modernization of grassroots governance. At present, the community health has not yet formed a perfect governance model, and in general, there are problems such as single governance body, uneven distribution of resources, imperfect mechanism and system, and prominent contradiction between supply and demand. As a new governance model for the management of public affairs, the concept of "equal consultation among multiple subjects" is in line with the development direction of China's "Co-construction, co-governance and sharing", and provides a new perspective for the construction of a multi-party community health governance model. Based on this, this paper takes the network governance theory as the analysis framework and Don Wai Floating Market, Nakhon Pathom Province as the research object. On the basis of clarifying the problems and causes of its community health governance, it puts forward countermeasures and suggestions for improving its community health governance model.